2019
DOI: 10.1021/acsomega.9b00751
|View full text |Cite
|
Sign up to set email alerts
|

Phenylpropanoid Glycerol Glucosides Attenuate Glucose Production in Hepatocytes

Abstract: An activity-guided fractionation approach revealed several phenylpropanoid glycerol glucosides isolated from the bulbs of Lilium longiflorum Thunb. (Easter lily) with gluconeogenesis inhibitory activities. The strongest activity was observed for (2 S )-1- O - p -coumaroyl-2- O -β- d -glucopyranosylglycerol ( 3 ), (2 S )-1- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Studies have shown that regalosides have anti-oxidation, bacteriostasis, anti-inflammatory and other functions. Murray et al [45] proved that phenylpropanoid glycerol glucosides can be used as an inhibitor of hepatic glucose production and may have potential to regulate metabolic syndrome and delay type II diabetes. The total glycosides of lily, including six regalosides, can protect cardiomyocytes by protecting mitochondria [46].…”
Section: Profiling Of Secondary Metabolitesmentioning
confidence: 99%
“…Studies have shown that regalosides have anti-oxidation, bacteriostasis, anti-inflammatory and other functions. Murray et al [45] proved that phenylpropanoid glycerol glucosides can be used as an inhibitor of hepatic glucose production and may have potential to regulate metabolic syndrome and delay type II diabetes. The total glycosides of lily, including six regalosides, can protect cardiomyocytes by protecting mitochondria [46].…”
Section: Profiling Of Secondary Metabolitesmentioning
confidence: 99%
“…Rosmarinic acid esters exhibited a broad spectrum of biological effects (Shen et al, 2018;Liang et al, 2017;Thammason et al, 2018). Glycerol phenylpropanoid glucosides act as hepatic glucose production inhibitors; structure-activity relationships indicated that the hydroxylation pattern of the hydroxycinnamic acid moiety and acetylation accounted for differences in activity (Murray et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Baihe Wuyao decoction (BWD), a prescription of Traditional Chinese Medicines, composed of Lilii Bulbus and Linderae Radix, has been used to treat epigastric pain and superficial gastritis for hundreds of years in China [3] . Previous phytochemical investigations indicated that Lilium contains several steroidal saponins, phenylpropanoid glycosides as well as phenyl glycosides [4–8] …”
Section: Introductionmentioning
confidence: 99%
“…[3] Previous phytochemical investigations indicated that Lilium contains several steroidal saponins, phenylpropanoid glycosides as well as phenyl glycosides. [4][5][6][7][8] To search for new bioactive constitutes of Lilium. Lilium regale Wilson was selected and three new chlorophenyl glycosides (1)(2)(3) were obtained from its bulb subsequently (Figure 1).…”
Section: Introductionmentioning
confidence: 99%